The Royal navy its influence in English history and in the growth of empire - Leyland, John (Cambridge manuals of science and literature, 2011)
The Royal Navy by John Leyland was first published in 1914. The book contains an account of the nature, character and development of the British Navy, revealing its roles in maintaining the security of the country and supporting the growth of the Empire.